Evaluation of spatio-temporal variations in water quality of Zerveli stream (northern Turkey) based on water quality index and multivariate statistical analyses - Mutlu, Ekrem (Springer Science and Business Media LLC, 2019)
This study of Zerveli stream, Kastamonu, aims to present an assessment of its water quality and to determine the basic factors having a significant effect on the water to identify how these factors account for variations in water quality. Samples of surface water were obtained on a monthly basis between December 2016 and November 2017 at 11 stations along the watercourse. According to these samples, 28 different water quality parameters determining the water quality were evaluated. The results were assessed with respect to the environmental water quality and irrigation water quality. For this purpose, the water quality index (WQI), sodium absorption rate (SAR), sodium percentage (%Na), and residual sodium carbonate (RSC) parameters were calculated. WQI values within the year ranged between 17.26 (excellent) and 223.05 (very poor). Based on the monthly mean values, the water quality was found to be good in December, February, July, and August and poor in the remaining months. Water quality tended to deteriorate the greater the distance from the water source. According to factor analysis (FA), salinity, pH, temperature (T), electrical conductivity (EC), suspended solid matter (SSM), chemical oxygen demand (COD), biochemical oxygen demand (BOD), SO42-, SO32-, NO2--N, NO-3-N, NH+4-N, and Cl are the main variables responsible for changes in the ecosystem. According to analysis of the irrigation water quality, the stream was found to be suitable for irrigation in terms of SAR (1.07-3.25) and %Na (37.58-61.89) but problematic in terms of RSC (3.80-5.58) values.
Keywords: Biological Oxygen Demand Analysis; Salinity; Turkey; Electric Conductivity; Rivers; Water Quality; Multivariate Analysis; Water Pollutants, Chemical; Environmental Monitoring; 15. Life on land; 6. Clean water; 13. Climate action; 14. Life underwater